1989
DOI: 10.1172/jci114087
|View full text |Cite
|
Sign up to set email alerts
|

Protection against nerve toxicity by monoclonal antibodies to the sodium channel blocker tetrodotoxin.

Abstract: The sodium channel blocker, tetrodotoxin (TDT), was conjugated to keyhole limpet hemocyanin (KLH) and used to immunize BALB/c mice. Anti-TDT antibodies were detected in serum by ELISA and reached stable levels 4-5 wk after the first immunization. Spleens from immunized mice were fused with NS-1 mouse myeloma cells and -9,329 resultant hybrids were screened by ELISA for reactivity to TDT. Two stable hybrids were isolated, subcloned, and characterized. These hybrids, termed TD13al and TD2C5, secreted specific an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
0

Year Published

1990
1990
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 24 publications
0
13
0
Order By: Relevance
“…The competition-inhibited enzyme immunoassay (CIEIA) described by previous report was used with modifications [11,25,26], the mixtures of TTX in a series of molar concentration (10 À3 -10 À7 M) and test antibody specimens in definite dilution of 10 À2 -10 À5 at which 50% antibody binding yielded by ELISA were incubated with BSA-TTX coated onto 96-well microtiter plate at 37 8C for 0.5 h. The plate was washed, then the GAM-HRP solution was added to wells and the rest steps were conducted same as above. In this assay system, the free TTX compete with BSA-TTX for specific antibody, and the binding of antibody to BSA-TTX was competitively inhibited to different extent by added varying conc.…”
Section: Determination Of Apparent Affinity (Kap)mentioning
confidence: 99%
See 1 more Smart Citation
“…The competition-inhibited enzyme immunoassay (CIEIA) described by previous report was used with modifications [11,25,26], the mixtures of TTX in a series of molar concentration (10 À3 -10 À7 M) and test antibody specimens in definite dilution of 10 À2 -10 À5 at which 50% antibody binding yielded by ELISA were incubated with BSA-TTX coated onto 96-well microtiter plate at 37 8C for 0.5 h. The plate was washed, then the GAM-HRP solution was added to wells and the rest steps were conducted same as above. In this assay system, the free TTX compete with BSA-TTX for specific antibody, and the binding of antibody to BSA-TTX was competitively inhibited to different extent by added varying conc.…”
Section: Determination Of Apparent Affinity (Kap)mentioning
confidence: 99%
“…Immunoprophylactic treatment was suggested as a new potential approach to protect animals against TTX poisoning. Early monoclonal antibodies to TTX could protect against TTX-induced nerve toxicity in vitro thereby used as useful regents for neurobiological research [11][12][13]. Fukiya and Matsumura [14] first reported active immunization for TTX.…”
Section: Introductionmentioning
confidence: 99%
“…Keyhole limpet hemocyanin-TTX-formaldehyde conjugate (KLH-TTXF) was prepared using a modification of the methods of Huot et al (12) and of Chu and Fan (14); 300 pl TTX (1 mgiml), 700 pl 1 M sodium acetate buffer, pH 7.4, 12 1 ~1 KLH (34.9 mg/ml), and 60 ~1 3 7 % formaldehyde were added dropwise (in that order), to an amber glas vial while stimng on a vortex mixer. The reaction mixture was then placed on a shaker and incubated at 37°C for 3 days.…”
Section: Klh-ttxf Conjugate Lmmunogenmentioning
confidence: 99%
“…They may also have a use as a diagnostic aid in suspected cardiac glycoside overdose involving dysrhythmias (Bagrov et al 1989) and in the treatment of pathological conditions such as eclampsia (Goodlin 1988(Goodlin , 1989 where 'endogenous digitalis' is postulated to have a role. Furthermore, drug-specific Fab fragments could have a use in the treatment of poisoning by other drugs and toxins such as phencyclidine (Owens & Mayersohn I986), desipramine (Hunting et al 1989) and tetrodotoxin (Huot et al 1989).…”
mentioning
confidence: 99%
“…Although digoxin-specific Fab fragments used clinically are derived from polyclonal antibodies raised in sheep, there is an increasing tendency to prepare rodent monoclonal antibodies which can be used in drug toxicity reversal (Mudgett-Hunter et al 1982;Bowles et a1 1988;Huot et al 1989). Indeed, it has been demonstrated that mouse monoclonal digoxin-specific Fab fragments effectively reversed the deleterious effects of a potentially lethal dose of digoxin in guinea-pigs (Lechat et al 1984).…”
mentioning
confidence: 99%